“And Now for the Rest of the Story”: The ITT and Vogeler/Sanders Case Revisited - Manchester, Margaret M. (Hungarian Journal of English and American Studies, 2022)
Robert A. Vogeler, an American businessman, served seventeen months in a Hungarian prison after being found guilty of espionage and economic sabotage. During his detainment and imprisonment, the US government used diplomatic and economic pressure to try to secure his release. Lucille Vogeler, a socialite, used personal diplomacy, the media, and contacts with underworld figures in Austria to pressure the US and Hungarian governments to release her husband. After their return to the US in 1951, the Vogelers became prominent critics of the Truman Administration’s policy of containment and urged their audiences, including many members of the US Congress, to wage a more aggressive campaign to defeat communism. Their experiences illustrate the ways in which the American business community and individual citizens contributed to the formulation of US Cold War policies. The case also illustrates the many ways in which media and public pressure could influence US foreign policy during the early Cold War years. (MMM)